Non-Operative Management Accelerates Recovery: Reduced Length of Hospital Stay in Partial Small Bowel Obstruction with Virgin Abdomens - Aryani, Prathita Amanda; Abdul Mughni (HM Publisher, 2025)
Background: Small bowel obstruction (SBO) represents a formidable challenge in surgical practice. Partial SBO (PSBO) in individuals without a history of abdominal surgery, termed